Evaluating The Efficiency Of Algerian Commercial Banks In Financing Economic Activity Standard Analytical Study For The Period "1990-2019" - أيمن فريد; زيراوي عادل (My University, 2021)
This study aims at analyzing the impact of the development of the Algerian banks efficiency on the growth of economic activity in light of the Monetary and Loan Law 90/10 reforms. It is based on the time series data for the period (1990-2017) and the multiple linear regression method using the least squares method (OSL). This is to reveal the impact of financial policy developments of the Algerian banking system on the growth of economic activity expressed in the gross domestic product at current prices. The study concluded that the effect of the financial policy channels of the Algerian banks on the growth of economic activity is limited, except for the effect of their expansion in lending to the national economy on the rate of inflation. تهدف هذه الدراسة إلى تحليل أثر تطور كفاءة البنوك الجزائرية على نمو النشاط الاقتصادي في ضوء إصلاحات قانون النقد والقروض 90/10. يعتمد على بيانات السلاسل الزمنية للفترة (1990-2017) وطريقة الانحدار الخطي المتعدد باستخدام طريقة المربعات الصغرى (OSL). وذلك للكشف عن تأثير تطورات السياسة المالية للنظام المصرفي الجزائري على نمو النشاط الاقتصادي المعبر عنه في الناتج المحلي الإجمالي بالأسعار الجارية.